Pengaruh Kompetensi, Budaya Organisasi, dan Komitmen Organisasi terhadap Kepuasan Kerja dan Dampaknya terhadap Kinerja Karyawan pada PT. Haji La Tunrung A.M.C di Makassar - Hawa Hardiyanti Abdullah La Tunrung; Fauziah Umar; Sumardi Sumardi (Magister Management, Hasanuddin University, 2019)
Competence is the ability of an individual to carry out a job correctly and has an advantage based on matters relating to knowledge, expertise, and attitude.This study aims to determine the effect of competencies, organizational culture, and organizational commitment on job satisfaction and its impact on employee performance at PT. Haji La Tunrung A.M.C in Makassar. The approach in this study is a quantitative. The population in this study were all employees at the company PT. Haji La Tunrung A.M.C. amounting to 48 people. The method of data collection is done using observations and questionnaires. Data were analyzed using path analysis. The results of this study indicate that (1) Competence has a positive and significant effect on job satisfaction in the company PT. Haji La Tunrung A.M.C in Makassar. (2) Organizational culture has a positive and significant effect on job satisfaction in the company PT. Haji La Tunrung A.M.C in Makassar. (3) Organizational commitment has a positive and significant effect on job satisfaction in the company PT. Haji La Tunrung A.M.C in Makassar. (4) Job satisfaction has a positive and significant effect on employee performance at PT. Haji La Tunrung A.M.C in Makassar. (5) The mediation test results that indicate that job satisfaction can affect the influence of competencies on employee performance in the company PT. Haji La Tunrung A.M.C in Makassar. (6) The mediation test results that show that job satisfaction can influence the influence of organizational culture on employee performance at the company PT. Haji La Tunrung A.M.C in Makassar. (7) The mediation test results that indicate that job satisfaction can mediate the influence of organizational commitment on employee performance in the company PT. Haji La Tunrung A.M.C in Makassar.